Experiences From The Italian High Speed Rail Network AV Construction - Vincent Jue (Deep Foundations Institute, 2010)
In December 2009, the Italian High Speed Rail Network AV began running over the full 1000 km system length from Turin, at the foothills of the Alps to Salerno, on the seacoast south of the volcano Mt. Vesuvius. It runs through Alpine rivers, highly seismic active zones, mountains, river plains, and through some of the most densely populated areas in Europe as well as some of its most expensive real estate. The Italian High Speed Network?s technical/economic constraints and its regulatory/socio-environmental concerns well may mirror similar obstacles set to confront the nascent California High Speed Rail Program. The two types of constraints must be dealt with together to reach the best construction solution. It is estimated that more than 20% of Italian High Speed Rail Network costs were spent on ground engineering including over 150 km of tunnels, 200 km of viaducts and bridges and 650 km of embankments and trenches. However, it also is estimated that 25% of costs were spent on social and environmental integration of the new rail lines including over 6 square miles of green offsets, 160 km of anti-noise walls, and 300 agreements for socio-environmental work. This paper will look at four examples of innovative ground engineering solutions, each with its own intricate set of constraints: ? Foundation system for viaducts across the ?Po? and ?Ticino? rivers. ? Soil consolidation under railway embankments ? Requirement of short tunnels for physical and environmental reasons ? Construction of railway stations in a confined right of way